2009
DOI: 10.1002/stem.143
|View full text |Cite
|
Sign up to set email alerts
|

KLF4 and PBX1 Directly Regulate NANOG Expression in Human Embryonic Stem Cells

Abstract: Insight into the regulation of core transcription factors is important for a better understanding of the molecular mechanisms that control self-renewal and pluripotency of human ESCs (hESCs). However, the transcriptional regulation of NANOG itself in hESCs has largely been elusive. We established a NANOG promoter luciferase reporter assay as a fast read-out for indicating the pluripotent status of hESCs. From the functional cDNA screens and NANOG promoter characterization, we successfully identified a zinc fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 67 publications
8
96
0
1
Order By: Relevance
“…35 The ability of NANOG to promote stem cell self-renewal and proliferation and to generate induced pluripotent stem cells has been well established. 17,18,20,[35][36][37] In this study, we have identified a novel role of NANOG in regulating FLK1 expression and angiogenic activity of ECs.Here, we show that NANOG is expressed in low levels in ECs and in a subset of tumor cell lines. Although the expression of NANOG is thought to be reduced in differentiated cells and tissues, our data show that NANOG is in fact present in mature ECs.…”
mentioning
confidence: 89%
“…35 The ability of NANOG to promote stem cell self-renewal and proliferation and to generate induced pluripotent stem cells has been well established. 17,18,20,[35][36][37] In this study, we have identified a novel role of NANOG in regulating FLK1 expression and angiogenic activity of ECs.Here, we show that NANOG is expressed in low levels in ECs and in a subset of tumor cell lines. Although the expression of NANOG is thought to be reduced in differentiated cells and tissues, our data show that NANOG is in fact present in mature ECs.…”
mentioning
confidence: 89%
“…5E). To determine whether forced expression of TRIM6 renders leukemia inhibitory factor (LIF) redundant in ES cells, as in the case of NANOG and KLF4 overexpression (Chan et al, 2009;Darr et al, 2006), we observed E14 cells stably expressing TRIM6 and mock cells without LIF. Although overexpression of TRIM6 in E14 cells caused high expression of NANOG, forced expression of TRIM6 could not maintain the undifferentiation of ES cells without LIF (Fig.…”
Section: Trim6 Regulates the Pluripotency Of Es Cells 1547mentioning
confidence: 99%
“…It was interesting to observe that there was EpICD binding to OCT-4 (distal upstream region) (52), NANOG (upstream region) (53)(54)(55), SOX2 (downstream region) (52), and KLF4 (upstream region) promoters as well, possibly suggesting that that EpCAM modulates ES phenotype through promoting the expression of these downstream targets (Fig. 7C).…”
Section: Suz12 and Jmjd3 Are Required For Bidirectional Regulation Ofmentioning
confidence: 99%